Coisas de menina: análise simbólica da personagem Buffy a Caça-Vampiros - Oliveira, Luísa de (2007)
The aim of this dissertation is to analyze the symbolical trajectory of Buffy, the Vampire Slayer, a character created by Joss Whedon in the 1990s. The show which tells Buffy s story consists of 144 episodes, which where considered a ratings phenomenon in many countries. In order to reach this objective, all 144 episodes were watched and schematized in summaries, which made it possible to identify and discriminate significant events, images and sequences in the composition of Buffy and her journey. The themes that seemed to be relevant at this point were closely related to the hero s archetype, which is the motivator of the process of the development of consciousness. Therefore, the analysis is based on C. G. Jung s concepts of analytical psychology and on Joseph Campbell s study of the heroic cycle. Buffy is regarded as a contemporary image of the hero s archetype. Throughout her journey, she was faced with seven challenges of growing complexity, which called for deep transformation and encompassed the formation of the persona, the withdrawal of projections, and the process of making aspects of shadow and animus conscious and integrated. Her trajectory is crowned with the possibility of transforming herself as well as her surroundings. In the first six confrontations, Buffy finds a way to save the world, but in the last (the seventh), she transforms it. In addition, vampire symbolism, serial characters and aspects pertaining to mass culture are discussed and interrelated